1396Trends in household food expenditure patterns by ethnic and income group in New Zealand. (2nd September 2021) - Nghiem, Nhung; Teng, Andrea; Cleghorn, Cristina; Wilson, Nick
Abstract: Background: Dietary factors are one of the most important risk factors for health loss worldwide, however there is very limited information on dietary trends in New Zealand (NZ) and whether inequities in dietary patterns are changing. Methods: We employed a validated economic dataset, the Household Economic Survey (HES), which was designed to provide information on impacts of policy-making in NZ. Three HES waves in 2006/07, 2009/10 and 2012/13 (n = 9030) were used to examine the trends in household expenditure for key food groups by income-level and ethnicity. Results: Overall, food expenditure per capita increased by 1% annually. In absolute terms, low-income households spent around half that of high-income households on food, but with no relative differences out of the total food expenditure or income. Māori households (Indigenous population) tended to spend less money compared to the other households, both in absolute and relative terms (ie, on healthy food including fruit and vegetables, and nuts and seeds, but with relatively more expenditure on processed meats). Similar food expenditure patterns by income-level and ethnicity persisted over time. Conclusions: HES data were useful for understanding trends in food expenditure patterns, in the absence of nutrition survey data, but limitations remain. Assuming food consumption is highly correlated to expenditure, diet inequities do not seem to have improved during this recent time period. Key messages: Public policies that aim to support healthy diets for all might need to involve changes to the food environment and involve government support for culturally appropriate Māori-led interventions.